2009
DOI: 10.3102/0034654309333844
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Three Types of Interaction Treatments in Distance Education

Abstract: This meta-analysis of the experimental literature of distance education (DE) compares different types of interaction treatments (ITs) with other DE instructional treatments. ITs are the instructional and/or media conditions designed into DE courses, which are intended to facilitate student–student (SS), student–teacher (ST), or student–content (SC) interactions. Seventy-four DE versus DE studies that contained at least one IT are included in the meta-analysis, which yield 74 achievement effects. The effect siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
598
2
35

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 881 publications
(658 citation statements)
references
References 55 publications
23
598
2
35
Order By: Relevance
“…This result was consistent with previous research which showed how interaction skills were more important than information skills for taking advantage of and being successful in online courses (Bernard et al 2009;Castaño-Muñoz et al 2014). …”
Section: Influence Of Digital Competence On Mooc Participationsupporting
confidence: 83%
“…This result was consistent with previous research which showed how interaction skills were more important than information skills for taking advantage of and being successful in online courses (Bernard et al 2009;Castaño-Muñoz et al 2014). …”
Section: Influence Of Digital Competence On Mooc Participationsupporting
confidence: 83%
“…Online learners may spend most of To increase learner-content interaction, it is necessary to understand the attributes of technologies that support interaction and instructional design that fits specific learning contexts (Anderson, 2003;Wagner, 1994). Compared to other settings (e.g., synchronous, hybrid), learner-content interaction has greater influence on learning outcomes in asynchronous settings (Bernard, Abrami, Borokhovski, Wade, Tamim, Surkes, & Bethel, 2009). Inclusion of tasks that involve collaboration and searching online resources may help enhance learners' interaction with content.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of student-student interaction is central to the design of online courses based on constructivist learning theories (Anderson, 2003) because constructivists believe that learners need to co-construct knowledge -and therefore to interact with each other -in order to learn and retain what they have learned (Jonassen, 1999). In higher education, student-student interaction in online courses has long been considered essential for both learning and for motivation (Bernard et al, 2009). In the K-12 online environment, the need for student-student interaction has been integrated into course quality standards (i.e., Southern Regional Education Board, 2006;iNACOL, 2011).…”
Section: Introductionmentioning
confidence: 99%